UJI EFEKTIVITAS ANTIBAKTERI EKSTRAK DAUN BINAHONG (Anredera cordifolia (Ten.) Steenis) TERHADAP ISOLAT BAKTERI Escherichia coli JAJANAN CILOK SECARA IN VITRO DENGAN METODE DIFUSI - Fadel Abima; Meiskha Bahar; Aulia Chairani (Jurnal Profesi Medika : Jurnal Kedokteran dan Kesehatan, 2017)
Diarrhea is still one of the world’s major health problem especially in developing country. Foods and beverages contaminated by microorganism become the risk factor of diarrhea, including Escherichia coli (E. coli). One of the curative effort that can be done is to utilise the secondary metabolite compounds contained in binahong leaf (Anredera cordifolia (Ten.) Steenis). This study used true experimental method. The sample was binahong leaf extract with concentration of 25%, 50, and 75% using diffusion method (Kirby-Bauer) on doublelayered Mueller Hinton Agar (MHA) (base layer and seed layer) in order to measure the growth inhibition zone around the cylinder plate. The amount of population on this study was 24 isolations of E. coli. The repetition of each treatment group was counted by Federer formula. The result analyzed using Kruskal-Wallis test and showed that there was difference on binahong leaf extract effectiveness (p < 0,05), as well as on post hoc analysis using MannWhitney test showed that there was significant difference at concentration of 25%,50%, and 75%. (p < 0,001). This shows that there is a significant differences in the concentration of binahong leaf extract.